Estudo de Proveniência das rochas metassedimentares do Complexo Ceará, na região de Sobral e adjacências, com base em datação U-Pb de zircão e idades-modelo Sm-Nd - FEITOSA, Jeremias Vitório Pinto (Universidade Federal do Pará, 2019)
The Borborema Province is an important tectonic province, with approximately 450,000 square kilometers in the northeastern Brazil, which registered numerous and remarkable geological processes that occurred on Earth over time. This province has great similarities with existing provinces in Africa, as the Benin/Nigeria. Successive geological cycles are recorded in rock types of the Borborema Province, dating back to a very complex geologic evolution started in the Archean, culminating at the end of the Neoproterozoic, with the occurrence of tectonic-thermal events and magmatism called the Brazilian Cycle, which resulted in the closure of an oceanic domain in this region. The Tamboril-Santa Quitéria Complex (TSQC) is the most significant unit of this final process of continental collision observed in Ceará Central Domain of the Borborema Province. The existent geochronological and isotopic data allow to understand the context and the geological evolution of the unit. However, for the metasedimentary rocks that flank the TSQC, assembled in the Ceará Complex, are lacking studies and information that permits to propose more refined geological models to better understand the evolutionary framework of this region. The suggested Paleoproterozoic age initially suggested for the metasedimentary rocks of Ceará Complex can questioned due to the presently known geological context. Thus, the sedimentary provenance study proposed here using U-Pb detrital zircon dating and Sm-Nd model-age (TDM), aims to investigate the maximum age of deposition of this metasedimentary unit, and the probable the crustal source of these rocks, to contribute to the understanding of the evolution and stratigraphic framework of Ceará Central Domain. This work included the sampling of 20 outcrops of these metasedimentary rocks that occur in the western and in the eastern flanks of the TSQC. Six samples of quartzite were collected for U-Pb zircon analysis using a laser ablation system attached to a multicollector mass spectrometer with inductively coupled plasma (LA-MC-ICPMS). Sm-Nd model-age determination was carried out in 14 samples. Petrographic study of the non-friable samples preceded the isotope analyses. The rocks of the western flanks of the TSQC were garnet gneiss and kyanite gneiss, with dominantly lepidoblastic and even granoblastic textures. Besides, sillimanite quartzite and muscovite quartzite occurs presenting polygonal granoblastic textures. In the eastern portion, the rocks were observed garnet gneiss with lepidoblastic and granoblastics textures in addition to garnet amphibolite with mainly nematoblastic and minor porphyroblastic textures. The Sm-Nd model-ages between 2.12 and 2.7 Ga., and positive values of Nd (2,1Ga) (+3.30 to + 2.60 ) suggests a strong contribution to Paleoproterozoic crust for the sediments located east of TSQC. This contribution is also recorded in the rocks sampled in the west of TSQC. However, TDM model-age of 1.66 Ga found in a rock also suggests contribution of younger crustal source for these metasedimentary rocks. The U-Pb data for quartzites of the Ceará Complex, in general, have prevalence of detrital zircons of Paleoproterozoic ages, more frequently of the Orosirian (1800-2050) and Rhyacian (2050-2300 Ma) periods, suggesting that the main source area of the sediments are Paleoproterozoic age. However the presence of detrital zircon grains of Statherian (1750± 50 , 1777± 58, 1628± 53 Ma) and Stenian age (1154 ± 29 Ma) found in rocks located east of TSQC indicates the input of younger rocks, corroborating the contribution of younger crustal source for the sedimentary succession of Ceará Complex. The age of 1154 Ma, indicates the maximum age of deposition of these sediments suggesting that this depositional event may even have occurred in the Neoproterozoic, as it is suggested by geological and geochronological evidences pointed out by some authors who studied this succession in other regions of Ceará Central Domain.